ANALISIS PENINGKATAN FREKUENSI PENCULIKAN DI LAUT OLEH ABU SAYYAF GROUP (ASG) PADA TAHUN 2016 - Jasmine, Rossiana; Wahyudi, Fendy Eko; Pertiwi, Sheiffi Puspa (Journal of International Relations, 2017)
In 2016, Abu Sayyaf Group (ASG) scored a new innovation in the field of kidnapping by abducting crews from sailing vessels around Southern Philippines sea. Then, the number of kidnapping with certain modus operandi increased. This study aims to determine factors that caused the increasing number of kidnappings at sea by the ASG in 2016. This study combines Martha Crenshaw’s Instrumental Terrorism approach (1988) that defines terrorism as a tool to fulfill the stated aim of a terrorist group with Peter Lehr’s Terrorist at Sea concept (2009) which stated that terrorist group often copies a tried-and-tested act by other group. This study uses literature study method through books, journals, reports and articles. Interview method with diplomats from the Ministry of Foreign Affairs of the Republic of Indonesia who were involved in the release of ASG’s hostages is also used to obtain supporting data. The result of this study is that three factors emerge as the cause of increasing number: the high probability in conducting the kidnappings; the comparison of gain and loss from the kidnappings, and the novelty behind the choice to kidnap. Other than that, ASG also conducted kidnappings at sea to reach its tactical aims in financial and recognition aspect, to maintain its sustainability, and to upgrade its social class among international terrorist network.